The State of Individual Alienation / Otherness in Oguz Atay's Novels - Sahin, Veysel (Rector Ciu Cyprus Int Univ, 2025)
Alienation is the plane of conflicts that emerges as a result of the individual, who lives within society, being unable to harmonize with themselves and with other entities outside of themselves. Each attempt to resolve these conflicts makes them increasingly complex. The individual, who represents the core of society, escapes from their current situation and declares war on themselves, their own self, and society. The fact that the 'subject I', which is the smallest building block of society, becomes alienated from itself and its self-values transforms it into an opposing force or the 'other' in relation to its inner values and layers of consciousness, both in thought and in action. This state of individual otherness, estrangement, and alienation arises as a result of the subject I's relationship-or lack thereof-with other subject-individuals or objects.O & gbreve;uz Atay, a significant figure in the modernization process of the Turkish novel, expresses the existential inquiries of alienation, otherness, loneliness, and angst, as well as the states of conflict experienced by the individual within themselves and society, through symbolic language in his fictional narratives. O & gbreve;uz Atay is a writer who persistently probes, wounds, and disrupts the inner world, the realms of self, and the consciousness of the individual. In fact, inAtay's novels, the alienation and otherness of the narrative subjects from their own imagined (thought-based) universe and values emerge in two forms: conceptual (imaginary/thoughtbased) and practical (action-based).In Atay's novels, the alienation and otherness experienced by the central narrative identities in their imagined and practical value worlds bring about dialectical processes such as change, transformation, conflict, angst, rebellion, escape, loneliness, personality fragmentation, and the construction of self, all of which unfold through one another. The conceptual alienation and othering of the subject-individual in Atay's novels stem from the individual's experience of emotional states such as angst, escape, fear, sorrow, and grief within their own realms of self. These negative conditions lead the subject-individual to conflict with and destroy their true self to the extent that they can no longer recognize it, and they eventually rebel against both themselves and their values.
Oğuz Atay’ın Romanlarında Bireysel Yabancılaşma/ Ötekilik Durumu
Keywords: O & gbreve;uzAtay; alienation; otherness; subject I; selfhood; conflict